MEDIATION MODEL OF CUSTOMER LOYALTY SAMSUNG SMARTPHONE DURING PANDEMI COVID 19 USING WARP PLS - Didik Gunawan; Dedy Dwi Arseto (Proceeding International Seminar of Islamic Studies, 2021)
This study aims to analyze the effect of innovation and features on customer loyalty mediated by customer satisfaction of Samsung smartphones. Respondents of this study were students of STIE BinaKarya who used Samsung smartphones. The results of hypothesis testing using SEM analysis with WarpPls show that innovation has no effect on customer satisfaction of Samsung smartphones, features affect customer satisfaction of Samsung smartphones, innovation has no effect on customer loyalty of Samsung smartphones, features have no effect on customer loyalty of Samsung smartphones, customer satisfaction affects customer loyalty smartphone Samsung, innovation affects customer loyalty Samsung smartphones mediated by customer satisfaction and features affect customer loyalty Samsung smartphones mediated by customer satisfaction. Based on these results, it is recommended that Samsung increase its smartphone product innovation, especially in the lower middle segment because many consumers consider Samsung to be stingy in innovation, especially during the Covid 19 pandemic, such as today where people's purchasing power has decreased sharply.. Keywords:Innovation, Features, Satisfaction, Loyalty, Smartphone